2003
DOI: 10.1148/radiol.2262011980
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Primary Hepatic Malignancy in Liver Transplant Candidates: Prospective Comparison of CT, MR Imaging, US, and PET

Abstract: Although US had the best diagnostic performance in depicting HCC on a patient-by-patient basis and was substantially better than were MR imaging and CT (which had nearly equivalent diagnostic performances), CT, US, and MR imaging performed similarly on a lesion-by-lesion basis. Small tumor nodules were the most common cause of missed HCCs with all tests. PET did not depict any HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
0
12

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(122 citation statements)
references
References 34 publications
0
109
0
12
Order By: Relevance
“…Eleven studies in this systematic review analyzed the accuracy of CT for the diagnosis of HCC [33][34][35]37,40,43,46,[48][49][50][51] (Supporting Table 5). Again, wide ranges were observed for the sensitivity (6%-100%) and the specificity (67%-100%), even though all studies except one 35 used the explanted liver as the gold standard.…”
Section: Question 3 What Are the Sensitivity And Specificity Of Nonimentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies in this systematic review analyzed the accuracy of CT for the diagnosis of HCC [33][34][35]37,40,43,46,[48][49][50][51] (Supporting Table 5). Again, wide ranges were observed for the sensitivity (6%-100%) and the specificity (67%-100%), even though all studies except one 35 used the explanted liver as the gold standard.…”
Section: Question 3 What Are the Sensitivity And Specificity Of Nonimentioning
confidence: 99%
“…Finally, 9 studies used MRI for the noninvasive diagnosis of HCC 32,40,43,46,48,[52][53][54][55] (Supporting Table 6). In all *The analysis was presented for 3 observers.…”
Section: Question 3 What Are the Sensitivity And Specificity Of Nonimentioning
confidence: 99%
“…Reported sensitivity values for CT range from 70 -80% (11)(12)(13), and MRI sensitivity of 84% was observed in a study with IV administered contrast agents (9). Thus, the traditional IV method of contrast agent delivery is inadequate for reliably detecting small HCC lesions.…”
mentioning
confidence: 99%
“…With this in mind, it should be emphasized that with conventional technology 16 and even with state-ofthe-art equipment, 17 we will always have some understaging, mostly caused by the failure to detect very small additional nodules less than 1 cm and/or microscopic vascular invasion. This was already emphasised years ago in the studies by Mazzaferro et al 6 and Llovet et al, 7 who reported this understaging after restrictive selection, but at the same time described its marginal impact on the recurrence rate after transplantation.…”
mentioning
confidence: 99%